Book Reviews. Issue 2 (1st October 2019) - Edwards, Emily; Martínez, Germán Martínez
The Iranian Diaspora Challenges, Negotiations, and Transformations, Mohsen Mostafavi Mobasher (ed.) (2018)Austin: University of Texas Press, 264 pp., ISBN 978-1-47731-664-1, h/bk, £27.99Living in Two Homes: Integration, Identity and Education of Transnational Migrants in a Globalized World, Mariella Espinoza-Herold and Rina Manuela Contini (eds) (2017)Bingley: Emerald Publishing Limited, 351 pp., ISBN 978-1-78635-782-3, h/bk, £73.99